Medical student career choice’s determinants in Asia: a systematic review - Rizma Adlia Syakurah; Rosyila Rosyila (International Journal of Public Health Science (IJPHS), 2020)
Asian countries have distinctive cultural patterns and norms that influence one’s decision making process throughout their life, including career choice. This review was intended to explore factors influencing medical students’ career choice in Asia. This review was compiled based on guidelines from PRISMA (Preferred Reporting Items for systematic reviews and Meta-Analysis). Data was searched and collected from studies published from electronic databases such as Pubmed, Europe PMC, Cochrane Databases, Science Direct, BMC Medical Education, ACM, Wiley Online Library and Mendeley with the keyword "medical student" and "career choice's determinants" or "medical students" and "career determinant" and "Asia". Six studies were found to match the inclusion criteria for this review. Five cross-sectional and one prospective cohort studies involving a total of 1.862 participants that were published between January 1986 and December 2017 were included. Among the included studies, the main findings were grouped into five main determinants: personal interest, family influence, prestigious profession, secure profession, and financial reward. Personal interest was the most influential factor that contributed to Asian medical student career choice’s determinants. It also highlights clinical specialist as unanimous career choice.